Safety and Accuracy of Suction Rectal Biopsy in Preterm Infants - Zhang, Yanan; Chen, Yongwei; Yang, Shen; Gu, Yichao; Hua, Kaiyun; Zhao, Yong; Huang, Jinshi (Frontiers in Pediatrics, 2021)
Purpose: Most pediatric surgeons give little attention to the diagnosis of Hirschsprung disease (HD) in preterm infants. We aimed to explore the safety and accuracy of suction rectal biopsy (SRB) for diagnosing HD in preterm infants. Methods: A retrospective review was conducted of 45 preterm patients who underwent SRB from 2015 to 2019 in our hospital. We collected the clinical characteristics and pathology results of the patients and information on follow-up. The sensitivity and specificity of SRB for HD diagnosis were calculated. Results: The median gestational age of the patients was 35 weeks (range: 28.9 to 36.9 weeks), the median gestational age at biopsy was 38.6 weeks (range: 33.4 to 60.0 weeks), and the median weight was 2790 g (range: 1580 to 4100 g). Fifteen patients (33.3%) were positive for HD, which was confirmed after pull-through surgery. Ganglion cells were present in 30 patients. The diagnosis of HD was excluded in 29 patients after discharge follow-up. The sensitivity of SRB ranged from 93.7-100%, and the specificity was 100%. No complications occurred after SRB among the patients whose biopsy age was < 37 weeks (10 patients) or biopsy weight was < 2000 g (5 patients). Conclusion: SRB is accurate and safe for diagnosing HD in late preterm infants.